An Unusual Cause of Oligoarthritis and Erythema Nodosum: Idiopathic Granulomatous Mastitis - Seçil VURAL; Pelin ERTOP; Koray CEYHAN; Hatice ŞANLI (Archives of Rheumatology, 2017)
Idiopathic granulomatous mastitis (IGM) is an unusual benign inflammatory disease of breast. Breast cancer mimics IGM both radiologically and clinically. However, IGM is a benign disease and awareness of such an entity prevents unnecessary surgical procedures. Although its etiology is unknown, it may be an autoimmune disease. There are few patients reported in the literature presenting with reactive arthritis and/or erythema nodosum accompanying IGM of breast. Granulomatous mastitis should be considered as a possible underlying cause of arthritis and erythema nodosum. In this article, we report this interesting association of IGM as an underlying cause of arthritis and generalized erythema nodosum in a 32-year-old female patient. Comprehensive examination for granulomatous mastitis showed no apparent underlying cause. Indomethacin was beneficial in treatment of arthritis and erythema nodosum. Resistant IGM was responsive to colchicine treatment. Clinical management and therapeutic approach have been discussed in detail.